2006
DOI: 10.1016/j.jasms.2005.12.015
|View full text |Cite
|
Sign up to set email alerts
|

Long-lived electron capture dissociation product ions experience radical migration via hydrogen abstraction

Abstract: To explore the mechanism of electron capture dissociation (ECD) of linear peptides, a set of 16-mer peptides were synthesized with deuterium labeled on the ␣-carbon position of four glycines. The ECD spectra of these peptides showed that such peptides exhibit a preference for the radical to migrate to the ␣-carbon position on glycine via hydrogen (or deuterium) abstraction before the final cleavage and generation of the detected product ions. The data show c-type fragment ions, ions corresponding to the radica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

17
156
0

Year Published

2007
2007
2014
2014

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 124 publications
(173 citation statements)
references
References 56 publications
17
156
0
Order By: Relevance
“…We believe there are several lines of evidence to support that these ions observed following EDD are Z ϩ 2H species. Hydrogen addition and abstraction following ECD of peptides have been well documented [60,59], and have also been reported for EDD of peptides [45]. Following EDD of GAGs, hydrogen abstraction from Band C-type ions has also been noted, and observed as B Ϫ H, C Ϫ H, and C Ϫ 2H type ions [32,33].…”
Section: Ms/ms Of Neutral Oligosaccharidesmentioning
confidence: 79%
“…We believe there are several lines of evidence to support that these ions observed following EDD are Z ϩ 2H species. Hydrogen addition and abstraction following ECD of peptides have been well documented [60,59], and have also been reported for EDD of peptides [45]. Following EDD of GAGs, hydrogen abstraction from Band C-type ions has also been noted, and observed as B Ϫ H, C Ϫ H, and C Ϫ 2H type ions [32,33].…”
Section: Ms/ms Of Neutral Oligosaccharidesmentioning
confidence: 79%
“…This picture is consistent with what is known about radical migration during ECD. In that case, the unpaired electron in an ␣-radical transfers stepwise to various other ␣-carbons, inducing a "radical cascade" of backbone fragmentations [33,36]. However, one cannot rule out the possibility that there is a similar distance dependence to the rate that radical ions fold.…”
Section: Kinetic Competition Between Radical Transfer and Charge-drivmentioning
confidence: 99%
“…Although O'Connor and coworkers have demonstrated that backbone ␣-hydrogens can be easily abstracted [36], it is still unclear whether backbone amidehydrogens are involved in the radical migration process. To address this issue, amide-hydrogens were replaced with deuterium by H/D exchange.…”
Section: Are Backbone Amide Hydrogens Transferable?mentioning
confidence: 99%
See 1 more Smart Citation
“…Particular advances have been achieved as a result of Fourier transform ion cyclotron resonance mass spectrometry (FT-ICR MS)-based electron capture dissociation (ECD) [4] complementarity to slow heating fragmentation methods [5], such as collision-induced dissociation (CID) [6] and infrared multiphoton dissociation (IRMPD) [7]. In addition to mainly product ion mass-based MS/ MS, product ion abundance (PIA) in ECD is increasingly considered as a new source of information to improve peptide and protein sequencing [8,9], quantitative modification analysis [10,11], higher-order structure characterization [8,[12][13][14][15], providing new insights into ECD mechanism [16,17], suggesting charge location in peptides and proteins [18,19], and indicating routes toward developing a quantitative model of ECD/ETD [15]. Double-resonance (DR) ECD, with and without ion preactivation, is used to estimate the radical intermediate lifetimes and differentiate between short-lived and long-lived intermediates by monitoring PIA variation attributed to radical intermediates ejection from the ICR trap immediately upon formation [20,21].…”
mentioning
confidence: 99%